2018
DOI: 10.1126/sciadv.aao7054
|View full text |Cite
|
Sign up to set email alerts
|

Insight into structural remodeling of the FlhA ring responsible for bacterial flagellar type III protein export

Abstract: Cooperative remodeling of the FlhA ring terminates hook assembly and initiates filament assembly at the hook tip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
102
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(105 citation statements)
references
References 45 publications
3
102
0
Order By: Relevance
“…FlhA acts as an energy transducer along with FliH, FliI and FliJ (Minamino, Morimoto, Hara, Aldridge, & Namba, ; Minamino, Morimoto, Hara, & Namba, ; Morimoto et al, ). The FlhA C ring provides binding sites for FliH, FliI, FliJ, flagellar export chaperones and export substrates along with the C‐terminal cytoplasmic domain of FlhB (FlhB C ) and coordinates flagellar protein export with assembly (Bange et al, ; Evans, Poulter, Terentjev, Hughes, & Fraser, ; Inoue, Morimoto, Namba, & Minamino, ; Kinoshita, Hara, Imada, Namba, & Minamino, ; Minamino, González‐Pedrajo, Kihara, Namba, & Macnab, ; Minamino et al, ; Minamino & Macnab, ; Terahara et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…FlhA acts as an energy transducer along with FliH, FliI and FliJ (Minamino, Morimoto, Hara, Aldridge, & Namba, ; Minamino, Morimoto, Hara, & Namba, ; Morimoto et al, ). The FlhA C ring provides binding sites for FliH, FliI, FliJ, flagellar export chaperones and export substrates along with the C‐terminal cytoplasmic domain of FlhB (FlhB C ) and coordinates flagellar protein export with assembly (Bange et al, ; Evans, Poulter, Terentjev, Hughes, & Fraser, ; Inoue, Morimoto, Namba, & Minamino, ; Kinoshita, Hara, Imada, Namba, & Minamino, ; Minamino, González‐Pedrajo, Kihara, Namba, & Macnab, ; Minamino et al, ; Minamino & Macnab, ; Terahara et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…At the core of the secretion system is the highly conserved export apparatus (EA) 4,5 , which is made up of five predicted transmembrane (TM) proteins (SctR, SctS, SctT, SctU and SctV in the vT3SS; FliP, FliQ, FliR, FlhB and FlhA in the fT3SS). FlhA/SctV has been shown to form a nonameric ring [6][7][8] , consisting of a large cytoplasmic domain situated below a hydrophobic domain predicted to contain 72 helices. This structure was proposed to surround an "export gate" through which substrates would enter the secretion pathway.…”
mentioning
confidence: 99%
“…For instance, in the Epsilonproteobacterium H. pylori, which has a three-tiered regulatory hierarchy of flagellar expression and assembly, including three sigma factors and a FlgM feedback loop (Niehus et al, 2004), researchers have found that several flagellar structural proteins are involved in flagellar regulation. These proteins include the basal body component FlhA, an essential part of the basal body and the assembly platform (Schmitz et al, 1997;Rust et al, 2009;Minamino et al, 2016a,b;Terahara et al, 2018) as well as FlhF, considered a signal recognition particle (SRP)like protein important for flagellar localization (Bange et al, 2007;Kazmierczak and Hendrixson, 2013;Kondo et al, 2017); additionally the TCSs FlgS-FlgR and ArsS-ArsR are involved (Pflock et al, 2006;Loh et al, 2010;Marcus et al, 2016;Xiong et al, 2019).…”
Section: Protein-protein Interaction Sensing In Flagellar Assembly Rementioning
confidence: 99%